2014
DOI: 10.4161/15384047.2014.955989
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles for the delivery of zoledronic acid to prostate cancer cells: A comparative analysis through time lapse video-microscopy technique

Abstract: Time-lapse live cell imaging is a powerful tool for studying the responses of cells to drugs. Zoledronic acid (ZOL) is the most potent aminobiphosphonate able to induce cell growth inhibition at very low concentrations. The lack of clear evidence of ZOL-induced anti-cancer effects is likely due to its unfavorable pharmacokinetic profile. The use of nanotechnology-based formulations allows overcoming these limitations in ZOL pharmaco-distribution. Recently, stealth liposomes (LIPOs) and new self-assembly PEGyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…[7][8][9][10] In fact, we found that stealth Lipo-ZOL induced a significant tumor growth inhibition in different cancer models such as prostate cancer or multiple myeloma compared to free ZOL and improved ZOL pharmacokinetics. [7][8][9][10] In particular, LIPOs showed the highest cytotoxicity compared to free ZOL and NPs on prostate adenocarcinoma cells, as evaluated by time-lapse video microscopy. 10 Moreover, we previously demonstrated that Lipo-ZOL was able to reach active concentrations in CNS.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…[7][8][9][10] In fact, we found that stealth Lipo-ZOL induced a significant tumor growth inhibition in different cancer models such as prostate cancer or multiple myeloma compared to free ZOL and improved ZOL pharmacokinetics. [7][8][9][10] In particular, LIPOs showed the highest cytotoxicity compared to free ZOL and NPs on prostate adenocarcinoma cells, as evaluated by time-lapse video microscopy. 10 Moreover, we previously demonstrated that Lipo-ZOL was able to reach active concentrations in CNS.…”
Section: Introductionmentioning
confidence: 81%
“…[7][8][9][10] In particular, LIPOs showed the highest cytotoxicity compared to free ZOL and NPs on prostate adenocarcinoma cells, as evaluated by time-lapse video microscopy. 10 Moreover, we previously demonstrated that Lipo-ZOL was able to reach active concentrations in CNS. When BBB permeability was altered such as in pathological states or chronic neuropathic pain, Lipo-ZOL was able to cross BBB and deliver ZOL in the brain or spinal cord by reducing neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations